Laboratory Population Parameters and Field Impact of the Larval Endoparasitoid Pseudapanteles dignus (Hymenoptera: Braconidae) on its Host Tuta absoluta (Lepidoptera: Gelechiidae) in Tomato Crops in Argentina - Nieves, Eliana Lorena (2014)
The tomato moth, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is a key pest of tomato, Lycopersicon esculentum L., crops in Central and South America. At present it is dispersing rapidly in Africa and Eurasian continents as an invasive pest, threatening worldwide tomato production. Pseudapanteles dignus (Muesebeck) (Hymenoptera: Braconidae) is an American endoparasitoid reported as the main natural enemy of T. absoluta in commercial tomato. To gain knowledge of the potential role of P. dignus in the biological control of this pest, we determined its population parameters in laboratory and the parasitoid’s impact on T. absoluta in the field. In laboratory, lifetime fecundity was 193 eggs per female, and longevity was 24 and 26 d for female and male, respectively. The finite rate of increase ( λ ) was 1.15 per female per day and the intrinsic rate of natural increase ( r m ) was 0.14. The net reproductive rate ( R 0 ) was found to be 51.2, and generation time ( T ) 28.8 d. The time for doubling the population ( DT ) was 5 d. Furthermore, field parasitism of T. absoluta varied between 33 and 64% in the different years studied. Population parameters estimated in this study can be considered baseline information for a mass-rearing protocol of this parasitoid. Moreover, growth rates of P. dignus , particularly r m , and its impact on field populations of T. absoluta indicated that this parasitoid is a valuable candidate for biological control of this pest.